Ulpia Topeiros. The Imperial Nomen Gentilicum in a city-title roman Thrace - Topalilov , Ivo (Studia Europaea Gnesnensia, 2022)
This paper explores the reasons why ἡ Τοπειριτῶν πόλις obtained the Trajanic nomen gentilicium Οὐλπία in its title. The question arises since it appears on the municipal coin series minted for Topeiros at a particular moment in time, specifically in 212 AD. This coincides with an imperial visit which Caracalla and his mother Julia Domna paid in the city. The author argues that by using such propaganda gimmick, the local authority sought to attract the emperor’s attention to the privileges and most probably territorial extension granted byTrajan but later delayed by Hadrian. The lands in question had originally belonged to the neighboring city of Abdera. It appears that the town leaders of Topeiros succeeded, since an in scription dated to the reign of Maximinus Thrax (235-238) shows a vast extension of the municipality’s landhold eastwards.